Theoretical Aspects of the Functioning of Startup Ecosystem - I. V. Marakhina (Цифровая трансформация, 2020)
The article examines the startup ecosystem and identifies its characteristics which determine the effectiveness and success of startups - the main producing elements of the system. The author points out the differences between startups and other small business entities, highlights their strengths and weaknesses, justifies the need to consider them within the ecosystems. The author identifies the micro and macro levels of the startup ecosystem which depend on the nature of the impact on startups. At the same time the article focuses on the development of the ecosystem itself, the factors that influence it are highlighted. The analysis of the elements of the startup ecosystem is carried out, the requirements for them are described, based on the results of the study is proposed a theoretical model of the startup ecosystem. The main characteristics of startups in the ecosystem are highlighted. The nature of relations with organizations and events providing startups with resources - the micro level of the ecosystem are described. A detailed assessment of the role of micro-level elements and their characteristics is given. The proposed model can be used to assess the level of development of a particular ecosystem, search for bottlenecks and problems of its functioning, and develop recommendations for creating and developing a startup ecosystem.